Produção de cimento:: Impactos Ã saúde e ao meio ambiente - Carvalho, Maria Beatriz Maury de; Blumenschein, Raquel Naves (Sustainability in Debate, 2012)
This article aims at showing the production process of cement identifying its impacts on human health, from the extraction of raw material, which generates degradation and contamination of the water and soil, to the emission of particulate matter, which causes respiratory tract diseases. In the Federal District, in the region of Fercal in Sobradinho, the existence of two large factories generates impacts on the health of nearby communities. In the Community Queima Lençol, located near one of these factories, pollution generated by the emission of particulate matter arising from the manufacture of cement, has caused serious respiratory problems in local people.